Transcriptome profiling reveals the underlying mechanism of grape post-harvest pathogen Penicillium olsonii against the metabolites of Bacillus velezensis - Zhang, Tingfu; Wen, Guoqin; Song, Bo; Chen, Zhenyong; Jiang, Shijiao (Frontiers in Microbiology, 2023)
Introduction Pathogen infection influences the post-harvest shelf life of grape berries. In a preliminary study, metabolites produced by Bacillus velezensis significantly inhibited the growth of the grape postharvest pathogen Penicillium olsonii. Methods To investigate the mechanism of interaction between B. velezensis and P. olsonii, a draft genome was generated for P. olsonii WHG5 using the Illumina NovaSeq platform, and the transcriptomic changes in WHG5 were analyzed in response to the exposure to B. velezensis metabolites (10% v/v). Results The expression levels of genes associated with sporulation, including GCY1, brlA, and abaA, were down-regulated compared with those of the control. In addition, spore deformation and abnormal swelling of the conidiophore were observed. The expression of crucial enzymes, including fructose 2,6-bisphosphate and mannitol-2-dehydrogenase, was down-regulated, indicating that the glycolytic pathway of WHG5 was adversely affected by B. velezensis metabolites. The KEGG pathway enrichment analysis revealed that glutathione metabolism and the antioxidant enzyme system were involved in the response to B. velezensis metabolites. The down-regulation of the pathogenesis-related genes, PG1 and POT1, suggested that B. velezensis metabolites decreased the pathogenicity of P. olsonii. B. velezensis metabolites disrupted the homeostasis of reactive oxygen species in P. olsonii by affecting glucose metabolism, resulting in spore deformation and disruption of growth. In addition, the expression of key pathogenesis-related genes was down-regulated, thereby reducing the pathogenicity of P. olsonii. Disscusion This study provides insights into the responses of P. olsonii to B. velezensis metabolites and identifies potential target genes that may be useful in biocontrol strategies for the suppression of post-harvest spoilage in grapes.